The age of stress science and the search for stability - Jackson, Mark 1959- (Oxford University Press, 2013)
An exploration of the history of scientific studies of stress in the modern world, revealing how the science that legitimates and fuels current anxieties about stress has been shaped by a wide range of socio-political and cultural, as well as biological factors